Pro ASP.NET 1.1 in VB .NET From Professional to Expert - Moroney, Laurence. (Apress : Imprint: Apress, 2005)
Pro ASP.NET 1.1 in VB.NET aims to be the definite reference for working developers in the field. Its compendium format covers every topic you are likely to come across in your day-to-day work, from handling data through to configuration and deployment. The books goal is to act firstly as a tutorial guide that can be read from cover-to-cover, then secondly as a reference book that you can scan quickly to retrieve the answer to a specific problem as you work. This book puts to use hard-won, real-world VB .NET experience, and demonstrates it clearly through numerous diagrams, screenshots, and working code samples.